A Technical Pearl to Ensure Reliable Harvest of the Anterolateral Thigh Myocutaneous Flap. Issue 3 (March 2015) - ALDeek, Nidal Farhan; Tsao, Chung-Kan; Kao, Huang-Kai; Wei, Fu-Chan
Abstract : Supplemental Digital Content is available in the text.